2019
DOI: 10.1093/icesjms/fsy207
|View full text |Cite
|
Sign up to set email alerts
|

Domesticated escapees on the run: the second-generation monitoring programme reports the numbers and proportions of farmed Atlantic salmon in >200 Norwegian rivers annually

Abstract: Norway is the world’s largest producer of farmed Atlantic salmon and is home to ∼400 rivers containing wild salmon populations. Farmed escapees, a reoccurring challenge of all cage-based marine aquaculture, pose a threat to the genetic integrity, productivity, and evolutionary trajectories of wild populations. Escapees have been monitored in Norwegian rivers since 1989, and, a second-generation programme was established in 2014. The new programme includes data from summer angling, autumn angling, broodstock sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 50 publications
3
51
0
Order By: Relevance
“…Drift diving has only recently (since 2014) been included as a standard method used in the Norwegian monitoring program of farmed escaped salmon (Glover et al 2019), supplementing the traditional method based on validation of fish gathered from angling (Diserud et al 2019, Glover et al 2019). Compared to angling-based methods of assessing the number and proportions of farmed escaped salmon (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Drift diving has only recently (since 2014) been included as a standard method used in the Norwegian monitoring program of farmed escaped salmon (Glover et al 2019), supplementing the traditional method based on validation of fish gathered from angling (Diserud et al 2019, Glover et al 2019). Compared to angling-based methods of assessing the number and proportions of farmed escaped salmon (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Retention of farmed fish within net pen facilities has greatly improved with time (Jensen et al 2010), yet escape events still occur at levels that pose a significant threat to wild populations of salmon (see Wringe et al 2018 for a recent example). To circumvent the ecological ramifications of escaped farmed salmon, various stakeholders have increased awareness and efforts to monitor the presence of escapees in wild populations (Glover et al 2019) and to mitigate the effects that can occur between wild and farmed salmon.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…hybridization) between wild and escaped Atlantic salmon Salmo salar from aquaculture operations have been documented across the natural range of the species where the 2 co-occur (Glover et al 2017, Keyser et al 2018. Escaped farmed Atlantic salmon regularly occur in both Europe and Atlantic Canada (Keyser et al 2018, Diserud et al 2019, Glover et al 2019 and have been commonly found in rivers at distances of up to 200 km from the nearest aquaculture site, although distant occurrences at sea have also been reported (Hansen et al 1993, Hansen & Jacobsen 2003, Jensen et al 2013. As a consequence, hybridization between wild and domestic salmon can be both spatially extensive and represent a significant proportion of a population's annual production (Glover et al 2013, Karlsson et al 2016, Sylvester et al 2018.…”
Section: Introductionmentioning
confidence: 99%